COMUNIDADES DE FAXINAL E SUAS DINÂMICAS SÓCIO-ESPACIAIS: DA FORMAÇÃO À DESAGREGAÇÃO DE UMA TRADIÇÃO NO MUNICÍPIO DE TIBAGI (PR) - Grzebieluka, Douglas (2010)
This research analyses the socio-spatial transformations occurring in rural communities of the Municipality of Tibagi (PR), particularly those whose occupational structure presented and / or characteristics common to faxinais. The faxinais are rural communities covered by the Araucaria Forests that make up the land use in a very particular and has two main spaces, a breeding community and the land to plant, separated by a fence or ditch. Was selected for the purpose of deepening the rural communities located west of the highway Transbrasiliana and river Tibagi. Having it as a case study of the Communities Faxinal of Empoçados, located in the district of Alto do Amparo and Faxinal of Mendes in the district of Caetano Mendes. Among the research methodologies used, stands the application of semi-structured questionnaires to older residents of these communities. In the economic dynamics experienced by Tibagi, from its beginnings to the present communities Faxinal had its heyday during the period called "Tropeirismo of Pig‖ in the first decades of the twentieth century. Since then, the modernization of agriculture and society have been introducing homogenizing process that left little room for these traditional communities, leading to breakdown of this tradition in the city.